Acknowledgment to Reviewers of Algorithms in 2021 - Algorithms Editorial Office (Algorithms, 2022)
Thanks to the great efforts of our reviewers, Algorithms was able to maintain its standards for the high quality of its published papers. Thanks to the contribution of our reviewers, in 2021, the median time to first decision was 15 days and the median time to publication was 35 days. Abdelkader Ouali Kyung-Yong Chung Abu Asaduzzaman Lars Rohwedder Adam Kolkiewicz László Juhász Adriana Burlea-Schiopoiu Laura Pierucci Ágnes Vathy-Fogarassy Laurens Muter Ahmed Mostafa Laurent Dewasme Albina Orlando Laurent Donzé Aleksandar Erceg Lenwood S. Heath Aleksander Król Leonardo Rundo Aleksandr Rakhmangulov Linas Petkevičius Alessandro Fedeli Lino De Oliveira Santos Alessio Martino Liqing Zhang Alexander Schaum Lorenzo Salas-Morera Alexandros Tzanetos Luc Jaulin Alexandru Banica Luigi Aldieri Alfonsas Misevicius Luís Cavique Ali Wagdy Mohamed Luis N. López De Lacalle Alok Mishra Luiz S. Martins-Filho Alwin Poulose Łukasz Knypiński Amir Mosavi Magdalena Wyrwicka Andras Farago Mahdi Rezapour André Bigand Mahmoud Elbattah Andrea Colagrossi Mahmoud El-Morshedy Andrea Serani Manuel Lafond Andrea Tangherloni Manuel Martinez Andreas Beham Marc Juarez Andreas Bück Marcelo De Carvalho Alves Andreas Kanavos Marcelo Kaminski Lenzi Andreas Keler Marco Antonio Amaral Andreas Schreiber Marco Gavanelli Andrej Sarjas Marco Jose Andries Engelbrecht Marcus Gallagher Andrzej Gnatowski Marde Helbig Andrzej Kasperski Maria Evelina Mognaschi Andrzej Pacana María Isabel Parra Arévalo Anna Borucka María J. Fuente Annunziata Esposito Amideo Marian Wysocki Anthony G. Constantinides Mário Basto Anthony Rossiter Mario Brcic Antonella Falini Mario Marinelli Antonello Rosato Mário Véstias Antonio De Leon Rodriguez Mariusz Topolski Antonio Jiménez-Martín Mariusz Uchroński António Miguel Rosado Da Cruz Mark Kelbert Arlindo Silva Marko Horvat Arnadi Murtiyoso Markus Rabe Arne Johannssen Martin Kenyeres Arseny Shur Masaki Ogura Artem Metlin Mateus Mendes Artur Jeż Matija Perne Ashok Kumar Patil Mauricio A. Sanchez Atanaska Georgieva Mau-Tsuen Yang Atefeh Hajijamali Arani Max Bannach Athanasios Tsadiras Mehdi Ghayoumi Audrius Banaitis Mehdi Neshat Aurélien Arnaubec Mehdi Salimi Baoye Song Meirav Zehavi Bariscan Yonel Miao Ling Wang Bartosz Sawik Michal Jasinski Basarab Matei Michal Kvet Begoña Guirao Michele Coscia Bhogendra Mishra Michele Leonardo Bianchi Binhai Zhu Miha Ravber Birgitta Dresp-Langley Mihaela Hnatiu Boris Aberšek Mikhail Oet Bruce Ndibanje Mikhail Tarkov Byung-Hoon Kim Miklós Krész Cagatay Iris Mikołaj Karpiński Calogero Vetro Minas Dasygenis Carlo Meloni Mingchang Chih Carmelo Majorana Ming-Xing Luo Chaman Verma Miriam Leeser Chih-Peng Fan Mitica Craus Christian Bongiorno M.L. Puertas Christoph Waibel Mohamed A. A. Ismail Christophe Chesneau Mohammad Ali Nilforooshan Christopher John Price Mohammad Ashrafuzzaman Christopher Martin Van Bommel Mohammad Bagher Dowlatshahi Christopher W. Cleghorn Mohammad Jafari Christopher Zimmer Mohd Nor Akmal Khalid Christos Makris Mohiuddin Ahmed Christos S. Antonopoulos Mohsen Rezvani Chrysafis Vogiatzis Monge Marco Antonio Sotelo Chung-Ping Chang Monica Berrondo Claudia Marzi Mostafa Mjahed Costas Vassilakis Muhammad Fahad Zia Cristian Lucian Stanciu Muhammad Shafiq Cristian Mihaescu Muhammad Syafrudin Cristian P. Lungu Mustafa Sarimollaoglu Cristina Martín Doñate Muzaffar Rao Cristina Requejo Nadia El-Mabrouk Dallan Byrne Nagham Saeed Daming Zhu Naomitsu Urasaki Dana-Mihaela Petroșanu Naveed Ahmed Azam Danica Rosinová Nguyen Quoc Khanh Le Daniel Rohacs Nhat Ho Daniela Briola Nick Bassiliades Daniele Frigioni Nick Pitropakis Daniel-Ioan Curiac Nikola Gradojevic Danilo Medeiros Eler Nikola Poljak Daniyal Haider Nikolai Krivulin Darío Garigliotti Nodari Vakhania Dariusz Horla Oliviero Carugo Darren A. Narayan Omar Darwish Davi Viana Otoniel Mario López Granado David Allouche Ovidiu Cosma David Lai Panagiotis D. Michailidis David Luengo Paolo Mercorelli David Sankoff Patricia Evans Davide Bilò Patricia Takako Endo Davide Fioriti Patricio Domingues Dawid Polap Patrick McClure Denis Delisle Rodriguez Paul Farago Diego Romano Paulo Ferreira Dilip K. Prasad Paweł Jabłoński Dimosthenis Kifokeris Paweł Weichbroth Diogo Poças Pedro Gómez Dmitry Bankov Per Håkan Lundow Dmitry Kosolobov Peter Von Zur Muehlen Dmitry Kruchinin Philip Bille Dmitry Lukyanenko Piergiuseppe Di Marco Dmitry Ruban Pierre Borgnat Dong Min Kim Piotr Gierlak Dusan Knop Piotr Miller Edorta Carrascal Lekunberri Plácido Moreno Beltrán Ehsan Bhuiyan Pratip Rana Eirini Eleni Tsiropoulou Qiangfu Zhao Elena M. Hernández Pereira Rachid Saadane Elena Nechita Radoslaw Michalski Elsa Cazelles Rafał Dreżewski Elzbieta Sidorowicz Ragnar Freij-Hollanti Emanuel Weitschek Rahul Singh Enrique Casarejos Raimo Kantola Erfan Maleki Ramiro Rico-Martinez Eric Tannier Ramyaa Ramyaa Erik Cambria Rashid Mehmood Ewa Roszkowska Rastislav Róka Fabio D'Andreagiovanni Razvan Bocu Fabrizio Balducci Rekha Guchhait Faranak Rabiei Renato Portugal Farzin Piltan Ricardo De Matos Simoes Federico Pittino Rita Girão Silva Felipe Martins Muller Rittika Shamsuddin Felix Albu Robertas Damaševičius Ferda Halicioglu Rodney Graham Downey Fernando Luis-Ferreira Rodrigo Righi Filippo Biondi Rodriguez Miguel Pineda Flavia Bonomo Romero Fernando Castaño Francesca Abastante Rossitza Goleva Francisco Cuevas De La Rosa Rui Zhang Franco Alberto Cardillo Saleh Mobayen Franya Franek Salman Ahmadi-Asl Freddy Gabbay Salvatore Corrente Furqan Aziz Salvatore Flavio Pileggi Fuyi Li Salvina Gagliano Fu-yuen Hsiao Sam Amiri Gaetano Salina Samad Noeiaghdam Gang Kou Sandy Brownlee Geneviève Simonet Sašo Karakatič Geoffrey Grime Sathishkumar Murugesan George K. Adam Satoshi Uchida George Matsopoulos Scott D. Flamm Georgios Alexandridis Sejong Oh Georgios Kostopoulos Seong-Ik Han Georgios Tsekouras Serafino Cicerone Gianni D'Angelo Serdar Durdyev Gilles Didier Sergei Sidorov Giordano Danilo Sergey Lashin Giorgio Audrito Sergii Babichev Giorgio Gosti Sevvandi Kandanaarachchi Giulia Caruso Seyed Mohammad Ghoreyshi Giuliano Zambonin Seyedali Mirjalili Giuseppina Inuso Shady H.E. Abdel Aleem Gokarna Sharma Shashi Raj Pandey Grzegorz Dombek Sheraz Aslam Guillermo Hauke Sherief Hashima Guillermo Valencia-Palomo Sherzod Turaev Guohao Dai Shinichi Yamagiwa Gupta Rajan Shmuel Tomi Klein Gustavo Pinto Shu-Chuan Chu Guy Mélard Shunsuke Shiraishi Gyanendra Prasad Joshi Simona Moldovanu György Dósa Sin-Jin Lin Han Zhang Slawomir Jarek Hanna Furmańczyk Socrates Basbas Hanno Hildmann Sotirios Kontogiannis Hao Wang Spyros Kontogiannis Haoran Chi Stanislav Harizanov Heike Trautmann Stefania Tronci Helbert Eduardo Espitia Stefano Antonio Gattone Helmut Ahammer Stefano Guerrini Hendrik Richter Stefano Seriani Hoai Nam Huynh Stefka Fidanova Hoang Nguyen Sung Jin Yoo Hongtian Chen Sung Wook Paek Ieva Meidute-Kavaliauskiene Sungho Suh Igor Vujović Sung-Hoon Mok Ilia Safonov Sungyong Choi Ilie Valentin Mihai Surender Reddy Salkuti Ilja Kröker Suxing Liu Indika Kumara Sven Bingert Ioannis Tsoulos Svetlozar T. Rachev Ionel Zagan Syed Tahir Hussain Rizvi Ionut Brandusoiu Sylvio Barbon Junior Iouliia Skliarova Szabolcs Duleba Iulian Grindeanu Tae-Eung Sung Ivan Izonin Taeho Kim Ivan Marović Tage Mohammadat Ivan Virgala Takuya Kida Ivana Kolingerova Talha Bin Masood Iwona Włoch Tamer Abdelmaguid Jaehyuk Choi Thaha Mohammed Jakub Nalepa Theodore Andronikos Jan Goedgebeur Thierry Lecroq Jan Van Casteren Thomas Espitau Jared Adolf-Bryfogle Thomas Kletschkowski Jaroslav Mlynek Thomas P. Karnowski Jarosław Figwer Tihomir Opetuk Jarosław Rybak Tom Huxford Jaroslaw Watrobski Tomas Balezentis Javier E. Contreras-Reyes Tomasz Górski Javier Oliver-Muncharaz Tome Eftimov Jean-Luc Prigent Travis Gagie Je-Keun Rhee Vadim S. Tynchenko Jens Heger Vaggelis Kapoulas Jerzy Rosłon Valdivieso Pedro A. Castillo Jianing Li Valentin Năvrăpescu Jianshe Ma Valentino Santucci Jie Hua Vanissorn Vimonsatit Jiří Škvor Vasile Daniel Pavaloaia Joana Alegria Quintela Vasilis Dimitriou João Pedro Barreto Vasiliy Elagin John Pryce Venanzio Giannella John R. Woodward Víctor Manuel Rivas Santos John Samuel Vikram Mulligan Jörg Rothe Violeta Kersuliene José Antonio Castellanos Garzón Viorel Minzu José Antonio De Diego Onsurbe Vittoria Cozza José Ramón Cardona Vittorio Bilò José Ramón Gaxiola-Camacho Vlad Diaconita José Santos Vladimir Stanovov Jozsef Katona Vladimir V. Semenov Juan Miguel Benito-Ostolaza Wojciech Sałabun Jude Hemanth Wolfgang Schreiner Julien Alexandre dit Sandretto Wookyong Kwon Junayed Pasha Xi Jin Juri Hinz Xiaoshuang Shi Juvenal Rodríguez-Reséndiz Xuefeng Zhang Karel Charvat Xunyuan Yin Karl Jones Yanfei Lu Karol Winkelmann Yeou-Jiunn Chen Karthikeyan Subramanian Yessica Nataliani Katarzyna Antosz Young-Seob Jeong Katarzyna Kaczmarek-Majer Yu Lin Kaustav Kundu Yu Tang Kazuyuki Takai Yuan Sun Kei Nakagawa Yuantao Gu Kenji Ikehara Yu-Chi Chung Kenneth Moreland Yuhu Wu Keshav Singh Yuji Iwahori Khushboo Munir Yung-Hui Li Kirill Kuzmin Yuri Pirola Komori Osamu Zbigniew Zakrzewski Konstantinos Giannoutakis Zelun Wang Konstantinos Syriopoulos Zeno Toffano Krzysztof Chwastek Zenon A. Sosnowski Krzysztof Klimaszewski Zhen Zhang Kyi Thar Zlatin Zlatev Kyungjoo Kim Publisher’s Note: MDPI stays neutral with regard to jurisdictional claims in published maps and institutional affiliations.